USING INFORMATION AND COMMUNICATION TECHNOLOGIES IN PEDAGOGICAL UNIVERSITIES - Djamirzayev A. A. (Bright Mind Publishing, 2025)
This article discusses the issue of increasing the competence of students in the field of communication technologies. In the modern educational process, communication technologies serve as an important tool for active communication among students, knowledge exchange and team work. The article discusses the main functions of communication technologies that determine the competence of students, as well as teaching methods and requirements for higher educational institutions. The authors suggest using effective methods to improve students' competence, including interactive methods, online courses and practical exercises. In short, communication technologies can improve the competence of students and make them effective members of society.
Keywords: ICT, communication, online platform, artificial intelligence, diagnostics, email, instant messaging, Big Data storage, Zoom, Google Meet, Slack, innovation.